Deixis Analysis of Drama “Trifles” by Susan Glaspell - Prasasti, Titah Gusti; Nadhif, Ahmad (ELITE JOURNAL, 2024)
The use of language in making meaning is strongly related to the context. This relation can be seen through deixis that refers to different things based on the speaker/writer’s intention. The hearer/reader’s ability to identify the referents is undoubtedly a necessity for a text to be comprehended. Deixis can be found in almost any text, including drama scripts like Trifles (1916) by Susan Glaspell. This research has two objectives. First, it aims at analyzing the types of deixis and its referents in the Trifles drama script by Susan Glaspell. Second, it is conducted to analyze the dominant type of deixis found in the script. This study applies the descriptive qualitative approach, in which the data are collected using documentation technique with five steps analysis data: 1) reading the dialogues, 2) identifying the deixis, 3) classifying deixis types, 4) describing the referents, 5) making a conclusion. The finding shows that there are 794 deictic expressions with various referents found in the drama script. It consists of 591 person deixis (74%), 62 place deixis (8%), 57 social deixis (7%), 52 discourse deixis (7%), and 32 time deixis (4%). Hence, the dominant type of deixis found in the drama script is person deixis.